The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4236/jep.2014.51002
|View full text |Cite
|
Sign up to set email alerts
|

Review: Current Status of Recycling of Waste Printed Circuit Boards in India

Abstract: Printed Circuit Boards (PCBs) are an integral part of any electronic equipment. The growth of e-waste as endof-life electronic equipments at an exponential rate is producing large quantities of discarded PCBs. In India, current recycling and processing of PCBs is managed almost entirely by the informal sector or the unskilled labor (95%). The crude recycling activities cause irreversible health and environmental hazards and the loss of valuable materials due to the poor recovery of base and precious metals. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It is revealed that the concentration of precious metals in one ton mobile phone is 3573 g silver, 368 g gold and 287 g palladium respectively (Chancerel et al, 2009). A study found that 1000 Kumar and Shah, 2014). It is also predicted that 6000 mobile sets weighing one tonne approximately would contain 130 kg Copper (United Nations University, 2009).…”
Section: Literature Reviewmentioning
confidence: 95%
“…It is revealed that the concentration of precious metals in one ton mobile phone is 3573 g silver, 368 g gold and 287 g palladium respectively (Chancerel et al, 2009). A study found that 1000 Kumar and Shah, 2014). It is also predicted that 6000 mobile sets weighing one tonne approximately would contain 130 kg Copper (United Nations University, 2009).…”
Section: Literature Reviewmentioning
confidence: 95%
“…The materials recovery priority varies with PCBs composition, selected ranking metric, and weighting factors within metrics [37]. From the technological point of view, current PCBs recycling approaches are high energy-demanding and environmentally dangerous processes, able only to recover about 30-35% of the metals present in PCBs, with variable purity levels going between 85% and 95% depending on the element [17,38].…”
Section: Pcbsmentioning
confidence: 99%
“…Electronic waste constitute heavy metals like lead, mercury, copper which are toxic to the environment if they leach directly into soil without proper recycling. Due to lack of appropriate technologies the increase in the volumes of the scrap is witnessed after informal recycling [11]. So there is a need to design a method by which the volumes of the toxic metals that are leached into the soil can be minimized without causing any harm to the environment.…”
Section: Characterization Of Magnetite Nanoparticlesmentioning
confidence: 99%